Adequacy of agency theory in explaining the venture capitalist-entrepreneur relationship: a firm life-cycle perspective. (2018) - Panda, Swati
This paper explores the adequacy of agency theory in explaining the venture capitalist (VC)-entrepreneur relationship through a firm life-cycle perspective. The findings indicate that advanced stage relationships suffer severely from agency risks while early stage relationships are less affected. The findings have important theoretical implications, as they propose boundary conditions along which agency theory can be applied to the VC-entrepreneur relationship. VCs and entrepreneurs can utilise the recommendations for better decision making, leading to an improved working relationship.